Open science and open access: A conceptual approach to ethics and information quality - Mejía-Ponce, Ma. Elieeneht (DIXI, 2023)
This review article is a conceptual approach to open science, open access, open data, research ethics, information quality and open research, among other elements closely linked to the open access approach. This article uses as a method the documentary research of the updated literature on the subject and makes a synthetic analysis of each concept. It was found that this paradigm of open science and open access is a current born in the 1990s that relies on technology and the interconnectivity of users to access quality scientific information. The network society is constituted as a social organization in the era of information and communication technologies (ict), where elements such as network connectivity, decentralization, collaboration, access to information, diversity and evolution, which are fundamental characteristics, coexist. The advantages provided by open data and open science are noted: transparency, citizen participation, innovation and creativity, and greater efficiency; without open science and open access implying a waiver of copyright. No less important, the ethics and moral values of our society apply to open access and open science to the extent that researchers maintain scientific integrity, transparency in their results, informed consent and non-manipulation of data. Thus, the binomial ethics and open access are closely linked and both are essential in research work.